IMPLEMENTASI TAT TWAM ASI DALAM PENYELENGGARAAN PEMERINTAHAN DI PROVINSI BALI - Diah Puspita Ernawati; I Gusti Ngurah Suwetha (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2020)
ABSTRACT. This research aims to analyze the implementation of “Tat Twam Asi” in the governance of the government in the Province of Bali. This research uses a descriptive method with a qualitative approach to obtain a complete picture of the implementation of Tat Twam Asi in the governance of the government in Bali Province. The data used are primary data sourced from informants that have been determined following the objectives of the research, while the secondary data obtained from collecting data relevant to the topic or problem that is the object of research. The concept of implementation used is the implementation of the Van Meter and Van Horn, specifically the implementation of actions by individuals, officials, government agencies, or private groups that aim to achieve the objectives outlined in individual decisions. Autonomy requires local governments to increase capabilities and effectiveness in running the wheels of government. Many local governments have not performed their functions and roles efficiently, and this can be observed from the numerous problems that have arisen; therefore, they must be followed by a series of public sector reforms. The dimensions of public sector reform change the format of institutions through the governance of the government by improving instruments that support the functioning of public institutions economically, efficiently, effectively, transparently and accountably in order to create good governance. Conducive conditions support the implementation of all activities in the governance of the government at every level of government. With conducive conditions, the governance of the government can be implemented following procedures that have been prepared and can operate smoothly, safely, naturally, and conveniently. In running the government, the Province of Bali always follows the paradigm of modern governance of the government in order to be able to create good governance while maintaining traditional values under Balinese customs, culture, and traditions, one of which is Tat Twam Asi. “Tat Twam Asi” is one of Hinduism teachings containing views on decency in social life, nation and state with a sense of tolerance, mutual respect, mutual admiration, and not behaving egoistically in making decisions when facing problems. Tat Twam Asi in the governance of the government is implemented starting from the government at the lower level, mainly Pakraman Village/Customary Village, to organize community life originating from the most basic level. The governance of government based on religion, tradition, and culture is very supportive of the activities of the regional government, such as when the local government will hold an activity that involves community participation and involves the leaders of the Customary Village (Desa Pakraman), in addition to the Official Village. The implementation of Tat Twam Asi in the governance of government in Bali Province is inseparable from the community's belief in the existence of the law of karma (karma phala), moreover that the teachings of ethics and decency are automatically applied to the level and order of life of the Balinese people including governance of the government. In this regard, a conducive atmosphere and conditions can be created in the governance of the government. Keywords: Implementation, Tat Twam Asi, and Governance of the Government.